Cell penetrating peptide decorated magnetic porous silicon nanorods for glioblastoma therapy and imaging. Issue 19 (14th April 2022) - Chaix, Arnaud; Griveau, Audrey; Defforge, Thomas; Grimal, Virginie; Le Borgne, Brice; Gautier, Gaël; Eyer, Joël
Abstract : Glioblastoma multiforme (GBM) is the most malignant primary brain tumor of the central nervous system. Abstract : Glioblastoma multiforme (GBM) is the most malignant primary brain tumor of the central nervous system. Despite advances in therapy, it remains largely untreatable, in part due to the low permeability of chemotherapeutic drugs across the blood–brain barrier (BBB) which significantly compromises their effectiveness. To circumvent the lack of drug efficiency, we designed multifunctional nanoparticles based on porous silicon. Herein, we propose an innovative synthesis technique for porous silicon nanorods (pSiNRs) with three-dimensional (3D) shape-controlled nanostructure. In order to achieve an efficient administration and improved treatment against GBM cells, a porous silicon nanoplatform is designed with magnetic guidance, fluorescence tracking and a cell-penetrating peptide (CPP). A NeuroFilament Light (NFL) subunit derived 24 amino acid tubulin binding site peptide called NFL-TBS.40-63 peptide or NFL-peptide was reported to preferentially target human GBM cells compared to healthy cells. Motivated by this approach, we investigated the use of magnetic-pSiNRs covered with superparamagnetic iron oxide nanoparticles (SPIONs) for magnetic guidance, then decorated with the NFL-peptide to facilitate targeting and enhance internalization into human GBM cells. Unexpectedly, under confocal microscope imaging, the internalized multifunctional nanoparticles in GBM cells induce a remarkable exaltation of green fluorescence instead of the red native fluorescence from the dye due to a possible Förster resonance energy transfer (FRET). In addition, we showed that the uptake of NFL-peptide decorated magnetic-pSiNRs was preferential towards human GBM cells. This study presents the fabrication of magnetic-pSiNRs decorated with the NFL-peptide, which act as a remarkable candidate to treat brain tumors. This is supported by in vitro results and confocal imaging.